Multi-objective Cooperative Optimization of Multi-heterogeneous Energy System Considering Energy Conservation - Quan CHEN; Xuanjun ZONG; Mengyuan LI (Zhongguo dianli)
The planning and operation of multi-heterogeneous energy systems often only considers a single optimization objective, which is not conducive to the balanced among economic operation, low carbon emission and energy conservation. This paper proposes a multi-dimensional objective collaborative optimization method that considers energy saving. Firstly, a multi-dimensional optimization objective is proposed with consideration of system economy, environmental protection and energy saving, and a multi-objective optimization model framework for multi-heterogeneous energy system is established by modeling energy conversion and distribution equipment in the system. Then, the NSGA-Ⅲ (non-dominated sorting genetic algorithm Ⅲ) is utilized to solve the multi-objective collaborative optimization model proposed in this paper, and the optimal feasible solution set (Pareto optimal solution set) is obtained. Finally, based on the simulation example, the effectiveness of the proposed method is verified through analysis of the optimal solution set and decision-maker preference. It is also demonstrated that considering the objective of energy conservation can avoid the system's excessive preference to consuming natural gas energy.